Budaya dan Identitas Tionghoa Muslim di Kalimantan Barat - Muhamad Murtadlo (Jurnal Lektur Keagamaan, 2013)
The community of Tionghoa muslim in Indonesia is a unique phenomenon. They are minority in number while they are also under minority tribes as Tionghoa. The uniqueness of them they hold onto majority religion in Indonesia.  The existence of this community was up and down in history. This study found the fact that there are cultural growth and identity in the present day, especially in the case of West Kalimantan. They formed the organization, adapted and has obsession to build Mosque with Tionghoa architecture. They plan for building Cheng Ho mosque.  Keywords: Muslim Tionghoa, Culture, and Identity.